(3eaGNQ GdebGd aj GdeUGOQ hGdCaYGds
(3ChdgG (B:s
(3GdMeO ddg GdPi cSGfG ef edGHS GdHjGf CSHZ SQHGd hHYO aJHjf dPi GdaWQI GdUMjMI GdRGcjI hGdaWfI GdUQjMI GdPGcjI eSjS MGLI GdTGQY ai eTGQY Ydhe GdTQY hSejJg eaGNQ GdebGd ai GdeUGQO hGdCaYGd s
(3BNQgG (B:s
( (3GdejcQhajde ZjQ hGVM ai GdJUhjQ (B) s
(3Yf ajde NGU HGdCSJGP (B/ (3CMeO eNJGQ fSeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdUQas